ANALISIS KEMAMPUAN AFEKTIF PESERTA DIDIK DALAM PEMBELAJARAN DARING PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 9 MALANG - Arina Tafrikhatus Solikhah; Ika Ratih Sulistiani; Arief Ardiansyah (VICRATINA, 2021)
Online Learning is an effort to transform learning into digital form assisted by internet technology, online learning is also one of the most effective learning because it is able to reach a very wide area. Affective ability in online learning Islamic Religious Education is very important because nowadays many people understand religious knowledge but are not necessarily able to practice it well, because affective values are not embedded in their hearts, and and religious values have not yet become a reflection their daily attitude. While the affective aspects of both spiritual attitudes and social attitudes as explained in the core competencies and basic competencies seem to be quite constrained when compared to classroom learning, affective learning carried out in the classroom is easier to implement because students interact with each other and face to face with teachers who concerned. While the assessment in the affective aspect carried out by online learning is more difficult for educators to do because educators do not pay attention to the behavior of students directly.